Nanosecond-range imprint and retention characterized from polarization-voltage hysteresis loops in insulating or leaky ferroelectric thin films - Jiang, A. Q.; Liu, X. B.; Zhang, Qi (American Institute of Physics (AIP), 2011)
We transferred ferroelectric domain switching currents under pulses into polarization-voltage (P-V) hysteresis loops. With this transformation, it is possible to derive the remanent polarization and coercive voltage from domain switching currents after the shortest imprint and retention time of 35 ns. After the separation of film leakage current from domain switching current, we measured the P-V hysteresis loop in a semiconducting BiFeO3 leaky thin film, where the apparent coercive field highly reaches 320 kV/cm2, suggestive of a different domain switching mechanism from other insulators. This technique facilitates nanosecond-range measurements of both ferroelectric capacitive and resistive memories.